The association between constipation and anxiety: a cross-sectional study and Mendelian randomization analysis - Huang, Yingxuan; Wang, Yubin; Xu, Boming; Zeng, Yilin; Chen, Peizhong; Huang, Yisen; Liu, Xiaoqiang (Frontiers in Psychiatry, 2025)
ObjectiveThe relationship between constipation and anxiety remains underexplored. This study investigates the association between constipation and anxiety in a representative sample of adults in the United States.MethodsA cross-sectional analysis was conducted using data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2010, including 9,126 adults aged ≥20 years. Constipation and anxiety were assessed using standardized survey instruments. Multivariable logistic regression models were employed to calculate adjusted odds ratios (ORs), and subgroup and sensitivity analyses were performed to validate the findings. Additionally, Mendelian randomization (MR) was employed to assess the potential causal relationship between constipation and anxiety using genetic data from large GWAS datasets.ResultsOf the 9,126 participants, 324 reported constipation (prevalence: 3.6%), and 2,424 reported anxiety (prevalence: 26.6%). Anxiety prevalence was significantly higher in individuals with constipation compared to those without (41.4% vs. 26.0%; P < 0.001). After adjusting for demographic, socioeconomic, lifestyle, and comorbid factors, constipation remained independently associated with anxiety (adjusted OR: 1.33, 95% CI: 1.02–1.73; P = 0.038). Subgroup analyses revealed no significant interactions. Sensitivity analyses, including multiple imputations, weighted analysis, and propensity score matching, corroborated the robustness of the results. MR analysis, however, revealed no significant causal association between constipation and anxiety.ConclusionThis study identifies a significant association between constipation and anxiety in a large, nationally representative cohort. While the association remains robust after adjusting for various factors, MR did not provide evidence for a causal relationship. Clinicians should consider evaluating and addressing anxiety symptoms as part of a comprehensive management strategy for patients presenting with constipation.